Mapping research trends in innovative pedagogies: a bibliometric analysis - Awang, Nurul Eeffah; Zulkifli, Hafizhah; Isa Hamzah, Mohd (Institute of Advanced Engineering and Science, 2025)
This study examines global research trends in innovative pedagogy through a bibliometric analysis of 901 Scopus-indexed publications from 2022 to 2024. Despite the growing importance of innovative pedagogy in modern education, a systematic evaluation of its research landscape is still limited. This study bridges this gap by analyzing key trends, including influential works, authors, citation networks, and emerging themes. Using VOSviewer for data visualization, the findings reveal a growing research focus on AI-driven learning, immersive technologies, and problem-based methodologies. The analysis highlights the social sciences as the dominant field (45.3%), with increasing contributions from computer science and engineering. The United States, Australia, China, and India emerge as leading contributors, while developing regions show an increasing presence in pedagogical innovation. Research indicates a shift towards digital and experiential learning environments, yet challenges such as digital accessibility, equity, and ethical concerns persist. The study underscores the importance of interdisciplinary collaboration and policy interventions to tackle these challenges. By providing a comprehensive overview of the research landscape, this study serves as a roadmap for educators, policymakers, and researchers to promote sustainable and inclusive advancements in innovative pedagogy.